Effect of silica on porosity, strength, and toughness of pressureless sintered calcium phosphate–zirconia bioceramics. (12th August 2015) - Schumacher, Thomas C; Treccani, Laura; Rezwan, Kurosch
Abstract: The preparation of dense, high-strength calcium phosphate–zirconia (CaP–ZrO2 ) composed bioceramics is realized via versatile pressureless sintering by adding silica nanoparticles. Two different weight ratios of HAp:ZrO2, 9:1 and 1:1, are used with varying silica contents from 5 to 20 wt%. After sintering at 1200 °C, the phase composition, microstructure, porosity, biaxial bending strength, and fracture toughness as well as SBF in vitro bioactivity are characterized. We show that the addition of silica altered the crystal phase composition, inhibiting the formation of non-favourable cubic ZrO2 . Furthermore, SiO2 addition leads to an increase of the biaxial bending strength, and the fracture toughness of CaP–ZrO2 -containing materials. With the addition of 20 wt% silica we find the highest characteristic strength (268 MPa) and toughness (2.3 ± 0.1 MPam 0.5 ) at <1% porosity. Both mechanical properties are 2 times higher than those of pure hydroxyapatite. At the same time we observe for the very same composition similar bioactivity to that of pure hydroxyapatite.